2011
DOI: 10.1007/978-3-642-24279-3_21
|View full text |Cite
|
Sign up to set email alerts
|

Smart Phone Sensing to Examine Effects of Social Interactions and Non-sedentary Work Time on Mood Changes

Abstract: Abstract. Study of mood and in turn mood changes is an important index of general wellbeing state and can also be an indicator of various mood disorders including clinical depression and bipolar disorder. While there have been clinical studies of mood, less emphasis has been placed on the factors that affect the mood, especially in workplace. The typical approach taken by these studies is to use clinical questionnaires in order to record the activities that impact the mood. However, recording activities that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
0
14
2
Order By: Relevance
“…Some of these features are quite creative and worth mentioning. The most promising results for the nonclinical samples include the time spent in break rooms (ρ=−0.21, nonsignificant) [16], and less SD of stillness amount, which can be interpreted as a more uniform activity pattern (beta=−3.3, P <.001) [46]. For the clinical samples, it includes the increased amount of time with no sound detection ( speech pauses ; beta=0.34, P =.004) [55], increased number of calls missed (beta=0.05, P =.006) [6], and fewer incidences of quick or sudden movements ( jerk ; t =4.06, P <.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these features are quite creative and worth mentioning. The most promising results for the nonclinical samples include the time spent in break rooms (ρ=−0.21, nonsignificant) [16], and less SD of stillness amount, which can be interpreted as a more uniform activity pattern (beta=−3.3, P <.001) [46]. For the clinical samples, it includes the increased amount of time with no sound detection ( speech pauses ; beta=0.34, P =.004) [55], increased number of calls missed (beta=0.05, P =.006) [6], and fewer incidences of quick or sudden movements ( jerk ; t =4.06, P <.001).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of detailed reporting on analysis methods was clearly demonstrated in a study by Beiwinkel et al [22], where a between-subject (cross-sectional analysis) relationship yielded a statistically nonsignificant ( P =.82) regression coefficient of −0.04, while a within-subject (longitudinal analysis) relationship yielded a statistically significant ( P =.03) regression coefficient of −0.11, on the feature of cell tower ID. Data aggregation length was also a concern because the duration of studies included in this review spans from 7 days [16,47] to 12 months [22]. Canzian & Musolesi [9] presented results on the correlation between PHQ-8 and different mobility features for 1 to 14 days of aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…One of the few studies to examine mood in the workplace using unobtrusive measures is a pilot study of nine information workers by Matic et al [31]. This study used smartphones to sense activity and correlated that with experience sampling of mood and active badges to detect social interactions.…”
Section: Related Workmentioning
confidence: 99%
“…The lack of detailed reporting on analysis methods was clearly demonstrated in Beiwinkel et al [21] where a between-subject (crosssectional analysis) relationship yielded a statistically non-significant (p = .82) regression coefficient of -.04, while a within-subject (longitudinal analysis) relationship yielded a statistically significant (p < .03) regression coefficient of -.11, on the feature of cell tower ID. Data aggregation lengths was also a concern since duration of studies included in this review spans from 7 days [16,48] to 12 months [21]. Canzian & Musolesi [9] presented results on the correlation between PHQ-8 and different mobility features for 1 to 14 days of aggregation.…”
Section: Limitations Data Collection and Analysis Methodsmentioning
confidence: 99%
“…A digital marker has been defined as a consumer generated physiological and behavioral measure collected from digital tool that can be used to explain, influence and/or predict health related outcomes [13]. Many studies have found statistically significant correlations between objective behavioral features collected from mobile and wearable technology and mood symptoms in non-clinical samples of participants without psychiatric illness (e.g., [14][15][16][17]) as well as in clinical samples of patients diagnosed with psychiatric disorders (e.g., [11,[18][19][20]), and this has raised great enthusiasm in terms of using mobile and wearable technology in the treatment and monitoring of depression and other affective disorders. It has been argued that such an approach may provide an easy and objective way to monitor illness activity and could serve as a digital marker of mood symptoms in affective disorders [18].…”
Section: Introductionmentioning
confidence: 99%